The Influence of Mobile Technologies on Employee’s Work Life Balance in Malaysia - Tan, Yie Hann (2014)
The influx of technological advancement have somehow changed the way we work and lives. Mobile technology, or so-called mobile device, is one of the greatest inventions that commonly used to perform a wide range of online activities and work tasks. Again, powerful functions embedded in these devices allow people to connect faster despite of geographical location and time period. In that case, work-life balance becomes a major challenge because different people may have different perception towards the impacts of using mobile technology. Certain part of people believed mobile technology usage brings flexibility, convenience and efficiency in balancing their work and life but some people argued there is an inverse relation to work-life balance. To answer this question, this research aims to assess the four factors (flexibility, addiction, time pressure and technostress) influencing work-life balance in Malaysia context. Structured questionnaire survey was conducted to 384 working adults at public places, such as train station, park and bus station within Klang Valley region (Kuala Lumpur, Shah Alam, Petaling Jaya and Subang Jaya) in Malaysia. Data were analyzed by using “Statistical Package for Social Science” (SPSS) and “Partial Least Square” (PLS) techniques. This research findings provide empirical evidence to managers, industries and government in managing work-life issues for creating a better life to employees.